2018
DOI: 10.1080/14786419.2018.1548445
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenolic compounds, in vitro antioxidant activity and characterization of secondary metabolites in different parts of Passiflora cincinnata by HPLC-DAD-MS/MS analysis

Abstract: Ethanol extracts of different parts of P. cincinnata were obtained by maceration. The total phenolic and flavonoid contents were evaluated. The antioxidant activities were determined by β-carotene-linoleic acid bleaching test, 2,2-diphenyl-1-picrylhydrazil (DPPH), and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging. The crude ethanol stem extract showed the highest amount of total polyphenols (45.53 mg gallic acid equivalent/g) while the highest total flavonoid contents (1.42 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Flavonoids are also one of the major components in S. tonkinensis . It is worth mentioning that the flavonoids have significant biological activities, such as anticancer (Lu et al, 2016), antioxidant (Aderogba et al, 2007; Leal et al, 2020), anti‐gastric ulcer (Sasajima et al, 1978), and antiviral (Dai et al, 2019). In addition, some studies have found that flavonoids in S. tonkinensis have potential toxicity (Liu, Zhu, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are also one of the major components in S. tonkinensis . It is worth mentioning that the flavonoids have significant biological activities, such as anticancer (Lu et al, 2016), antioxidant (Aderogba et al, 2007; Leal et al, 2020), anti‐gastric ulcer (Sasajima et al, 1978), and antiviral (Dai et al, 2019). In addition, some studies have found that flavonoids in S. tonkinensis have potential toxicity (Liu, Zhu, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This plant species is well adapted to local cultivation conditions in northeastern Brazil and highly resistant to pests and diseases (Araujo, 2007). Passiflora cincinnata has been found to have aromatic metabolites, substances with antimicrobial activity and antioxidant potential, and is able to reduce nociceptive and inflammatory events in mice (de Lavor et al, 2018;Leal et al, 2018;Siebra et al, 2018). These beneficial properties are important features when evaluating P. cincinnata as a potential producer of novel bioactive compounds that could be exploited by the food and pharmaceutical industries (Joana Gil-Chávez et al, 2013).…”
Section: Short Communicationmentioning
confidence: 99%
“…Passion fruit is widely used in Brazil, especially in the northeastern region, for preparing beverages and in popular medicine, because of its potential applica-tion as a sedative, antioxidant, and anxiolytic (Dhawan et al, 2004;Leal et al, 2018). It is well known that extracts of certain plants can increase the quality and sensory attributes of foods because of their antimicrobial and antioxidant activity and the presence of pleasant aromatic compounds and coloring characteristics; however, these extracts must be characterized before proper application (Tayel et al, 2013).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Foram identificados 14 flavonoides, previamente descritos em outras espécies de Passiflora. 52 O extrato etanólico bruto das folhas também apresentou atividade antinociceptiva e anti-inflamatória in vivo. 53…”
Section: Passiflora Cincinnata Mast (Passifloraceae)unclassified